Modeling protein adsorption onto lipid monolayer surface - Trusova, V. M. (Biophysical Bulletin)
Using the modified Frumkin approach, the adsorption of protein onto the surface of lipid monolayer has been simulated allowing for the different types of protein-lipid interactions. The results were presented in terms of the monolayer surface pressure increase induced by protein sorption (  ) as a function of initial surface pressure ( 0). The simulated curves were obtained under varying a range of interaction parameters. It was suggested that the trend of 0  ( ) plot allows to distinquish between protein interfacial localization and its penetration into lipid monolayer. The theoretical predictions are in accord with the experimental observations available in literature